MEMBANGUN SMART APARATUR SIPIL NEGARA (ASN) MELALUI PELATIHAN - Aan Nopriandi (Jurnal Perspektif, 2022)
This study aims to examine the development of state civil apparatus (ASN) resources through training in building Smart ASN towards bureaucratic reform. In this study, the method used is "Literature Review" which contains reviews (Compare, Contrast and Synthesize), summaries (Summarize), and author's thoughts (Criticize) from several library sources related to Smart ASN. The results of this study show that Smart ASN must have and master technology, even be able to engineer and make various applications in realizing excellent public services to the community; must also have a high sense of nationalism by applying or implementing the principles of good governance; have a sense of responsibility as well as empathy . The conclusions obtained in connection with the training in building the Smart ASN, it is necessary to make improvements in several ways including: competency-based training with curriculum development and adjusting to the current curriculum model desired as needed, it is hoped that the results of the curriculum development can produce ASN graduates or training alumni with the desired ability standards. In the end, this competency-based training is expected to be able to build and develop professionalism and Smart ASN in realizing bureaucratic reforms towards world-class government.